Peran Perempuan Karir Membangun Komunikasi Positif Interpersonal dalam Keluarga Multikultural - Khaerunnisa Tri Darmaningrum; Ahmad Hidayatullah (LPPM IAIN Parepare, 2020)
This research seeks to uncover the role of women in building positive interpersonal communication in multicultural families. One of the roles of women in the family is to build positive interpersonal communication within the family. Where in interpersonal communication patterns there is a dependency of each individual to face each other face to face. But ignorance is a major problem of communication in multicultural families. The qualitative descriptive method of phenomenology in this study was used to uncover the social psychological aspects experienced by women when she had a role as a builder of active interpersonal communication in her family. This research was conducted on working women speakers who have large families from various races. In addition, researchers also conducted a literature study on interpersonal communication theory that could be applied in multicultural families and women's psychological theories. In this study it was found that the role of women in building active communication in their families is very important.